A novel method to produce kiss-bonds in composites components for NDI and characterisation purposes - Telford, R.; O'Carroll, A.; Pierce, R.S.; Young, T.M. (2019)
Kiss-bonds (kissing bonds) are a defect type that feature a localised loss of structural continuity within the material, yet the material remains in intimate contact across the defect. Typically, shear and normal tensile stresses cannot be conducted across such defects (although, pure compressive stresses are possible). Kiss-bond defects are difficult to detect reliably – both within the bulk of the material (interlaminar) and within bond-lines of adhesively bonded joints or repairs – using conventional Non-Destructive Inspection (NDI) techniques. Compounding this issue is the lack of a reliable technique to create representative kiss-bond defects in a controlled fashion for the purpose of NDI equipment calibration or development, or scientific investigation. A novel method for manufacturing composite material test panels with kiss-bond defects (for research or NDI calibration, for example) in a controlled and repeatable fashion has been developed. Small areas of two adjacent pre-preg plies were pre-cured before being incorporated within a laminate. During consolidation, no bonding occurs between the pre-cured areas, thus creating a kiss-bond defect of known geometry. Test panels with 6 × 6 mm and 10 × 10 mm kiss-bond defects were manufactured. The robustness of the technique was verified using ultrasonic and laser shearography NDI methods; 7 of the 10 manufactured defects were classified as kiss-bonds, with the remaining 3 identified as dis-bonds.